Exploring the Role of Accommodation Contracting in Travel Agent Service Delivery - Hadisukarno, Teguh; Prasasti, Galih; Rahjasa, Putu Surya Laksana (Institut Pariwisata Trisakti, 2025)
This study aims to analyze the effectiveness of the accommodation contracting process in supporting travel agent services, with a case study at EXO Travel Indonesia. The research identifies key issues such as delays in contract finalization, mismatches between contract prices and reservation system entries, and limited internal coordination, all of which can impact service quality and operational efficiency. Using a qualitative approach, data were collected through in-depth interviews, direct observation, and documentation over a six-month period involving 25 respondents from internal teams and hotel partners. The data were analyzed through processes of data reduction, presentation, and conclusion drawing with ongoing verification. Findings reveal that while the contracting process is generally effective, it still faces administrative and communication challenges. Nevertheless, the presence of clear, detailed, and flexible contracts contributes positively to service delivery by enhancing client satisfaction and strengthening relationships with accommodation partners. The study also finds that service effectiveness is significantly supported by the clarity of contractual information and the proactive role of the contracting team in ensuring smooth cross-department coordination. These insights emphasize the importance of a streamlined and collaborative contracting process in delivering efficient and high-quality services within the travel industry. Keywords: effectiveness, contract process, accommodation, travel agent